CULTURE AND FOREIGN LANGUAGE TEACHING: THE MISSING FORMULA OF YEMENI ENGLISH TEACHERS/LEARNERS - Mohammed Hejash (English Department, STKIP PGRI Bandar Lampung, 2021)
The study is not only designed to measure up the degree of cultural awareness while learning/ teaching the English language, but it also helps in finding out how mother tongue culture can severely affect our everyday acquired language in the context of Yemen. The researcher has used the pragmatic approach tools to highlight all the cultural impacts and elaborated the importance of making Yemeni teachers aware of this approach. Culture could really play an important role in the quality of English one ought to learn and teach so the researcher has attempted to find out remedial methods to get rid of all the confusion that culture causes and help teachers identify such a learning/teaching fallacy.